Meiotic cohesin SMC1β provides prophase I centromeric cohesion and is required for multiple synapsis-associated functions. - Uddipta Biswas; Cornelia Wetzker; Julian Lange; Eleni G Christodoulou; Michael Seifert; Andreas Beyer; Rolf Jessberger (PLoS Genetics, 2013)
Cohesin subunit SMC1β is specific and essential for meiosis. Previous studies showed functions of SMC1β in determining the axis-loop structure of synaptonemal complexes (SCs), in providing sister chromatid cohesion (SCC) in metaphase I and thereafter, in protecting telomere structure, and in synapsis. However, several central questions remained unanswered and concern roles of SMC1β in SCC and synapsis and processes related to these two processes. Here we show that SMC1β substantially supports prophase I SCC at centromeres but not along chromosome arms. Arm cohesion and some of centromeric cohesion in prophase I are provided by non-phosphorylated SMC1α. Besides supporting synapsis of autosomes, SMC1β is also required for synapsis and silencing of sex chromosomes. In absence of SMC1β, the silencing factor γH2AX remains associated with asynapsed autosomes and fails to localize to sex chromosomes. Microarray expression studies revealed up-regulated sex chromosome genes and many down-regulated autosomal genes. SMC1β is further required for non-homologous chromosome associations observed in absence of SPO11 and thus of programmed double-strand breaks. These breaks are properly generated in Smc1β⁻/⁻ spermatocytes, but their repair is delayed on asynapsed chromosomes. SMC1α alone cannot support non-homologous associations. Together with previous knowledge, three main functions of SMC1β have emerged, which have multiple consequences for spermatocyte biology: generation of the loop-axis architecture of SCs, homologous and non-homologous synapsis, and SCC starting in early prophase I.